“L’OPERA SERIA” ET SES RÉFORMES - TODEA, Diana (Studia Universitatis Babes-Bolyai Musica, 2014)
Melodrama or dramma per musica are terms describing the opera genre that was used for more than a century since its appearance. This genre states literary pretensions and reinforces the principle that governed this period, namely that the opera is nothing but "a solid branch of dramatic literature."[1] In the early eighteenth century it was intended to save this "spectacular show" and purify it of all the adjacent and useless elements - overlapping plots, numerous characters, the mix of tragic elements and of puffs, abundant scenery and scenic machineries etc. The initiative come in this context from the men of letters. This reform, which was first of all a literary one led to the development of opera seria; half a century later, when one would focus again on the innovations of the genre there will be a second reform, this time more than dramatic since it will have solid musical and theoretical foundations. [1] «L’opéra ne constituait que un branche sur un tronc solide de la littérature dramatique», in Isabelle Moindrot, L’opéra seria ou le règne des castrats [Opera seria or the reign of the castrati],.Paris, Fayard,1993, p. 21.